Pengaruh Metode An-Nashr Terhadap Perbendaharaan Kosakata Bahasa Arab Di Madrasah Diniyah Takwiliyah Awaliyah Hidayatulloh Bangsal Mojokerto - Nailin Nishfi Fajriyah (Impressive: Journal of Education, 2023)
Arabic is a foreign language for foreign speakers who have a mother tongue other than Arabic.  As a foreign speaker, to expand the understanding of Arabic is to multiply the mastery of each meaning of the Arabic vocabulary. In this case, to multiply the vocabulary treasury is to use the an-Nashr method. The purpose of this research are: 1) to determine the effect of the an-Nasr method on Arabic vocabulary at Madrasah Diniyah Takwiliyah Awaliyah Hidayatulloh Bangsal Mojokerto. 2) to find out the obstacles and supporters of the an-Nasr method on Arabic vocabulary at Madrasah Diniyah Takwiliyah Awaliyah Hidayatulloh Bangsal Mojokerto. In conducting this research, the researcher used a descriptive quantitative approach using research instruments in the form of questionnaires, interviews, documentation, and observations. The data were analyzed with the coefficient of determination and simple linear regression, presented the data, and drew conclusions. The results of this study are: 1) Arabic vocabulary acquired by students increases by 72.7%. 2) The results of this study indicate that there is a positive effect of the an-Nasr method on Arabic vocabulary with a significant level of 0.001. So it can be concluded that Ho is rejected and Ha is accepted.